Organizational social capital Scale based on Nahapiet and Ghosal model: development and validation - Fandiño, A. M.; Marques, C.; Menezes, R.; Bentes, S. R. (Review of Contemporary Business Research, 2015)
The goal of this work is to develop and validate a scale to identify workers' behaviors as well as those of organizations, and to understand how they develop and build enterprise competitiveness through organizational social capital, a complex network of relationship that is critical to business success. For this the present theories were mapped out to identify the similarities and differences within social capital, focusing on organizational social capital. With this background a Nahapiet and Ghosal three dimensional model was chosen as the most suitable construct with which to create the instrument. All methodological research steps for behavioral instrument creation were taken into account. The questionnaire created was refined and validated for semantic and content validity, then it was tested using statistical tools for items reduction through Exploratory Factor Analysis to refine the instrument. The scale was approved in the tests and the findings of this process also led to the conclusion that social capital is a one-dimensional construct.